Applied current on the suppression of strontium segregation in Sr₂Fe₁.₅Mo₀.₅O₆₋δ electrode for improved oxygen evolution reaction - Li, Hao-Yang (2023)
Strontium surface segregation is the main issue that causes long-term performance degradation in strontium-containing electrodes for solid oxide electrolysis cells. In this research, we effectively suppress strontium segregation by applying an anodic current that drives the segregated strontium back to the perovskite lattice and mitigate electrode performance degradation. By monitoring the impedance of Sr2Fe1.5Mo0.5O6-δ (SFM) air electrode under open circuit voltage at high temperature with changing current densities over time, the degradation caused by strontium segregation is verified. The applied current successfully prevent the polarization resistance from increasing is observed. The cell with 0.8 A/cm2 of the applied current increase only 3% of polarization resistance as compared to the cell without applied current after testing at 800 ℃ for 24 h. The atomic ratio of strontium on the SFM electrode surface shows lower strontium content after undergoing applied current, which means that the strontium is indeed migrated back to perovskite lattice under the applied current and result in slower degradation of the SFM electrode.